Assessing the impact of mobile consolidation on innovation and quality: An evaluation of the Hutchison/Orange merger in Austria - Xavier Pedrós; Kalvin Bahia; Pau Castells; Serafino Abate (International Telecommunications Society (ITS), 2017)
Assessing the impact of a merger – or predicting the impact of a merger – follows competition law and relies on economic practice. Competition authorities strive for consistency of approach, with assessments generally based on an analysis of the impact on prices, quality and innovation for consumers. Experience has shown, however, that the main measurement relied on by competition authorities is pricing; could the proposed merger increase prices in the short-term? How harmful would this be for the consumer? In the case of mergers in general, and mobile mergers in particular, we argue that whilst price is an important factor, there has been an over reliance on this single aspect of consumers outcomes and less consideration of quality and innovation.
Keywords: 330